Client’s violence towards social workers - Sousa, Sara; Silva, Isabel; Veloso, Ana; Tzafrir, Shay; Enosh, Guy (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
The aim of this study is to characterize clients’ violence towards social workers, in terms of its frequency, as well as identify the organizational measures used to reduce and manage work related violence. Data were collected within 2 different stages which involved the use of interviews and questionnaires and included a total of 108 employees and 27 managers. The results indicate that at least half of the participants were victims of clients’ violence and verbal aggression is the most common type of violence. Finally, the results also revealed a set of measures of primary, secondary and tertiary intervention which are being used by the organizations involved in this study.